A quantitative study of bone defects in displaced femoral neck fractures based on virtual reduction techniques. (July 2022) - Zhu, Xiao-zhong; Han, Chun-xia; Ai, Zi-sheng; Wang, Wei; Wu, Sheng-hui; Zhao, Ke-yang; Liao, Peng; Mei, Jiong
Highlights: Qualitative analysis of bone defects in femoral neck fractures has already been performed, quantitative studies have not been reported. With this in mind, a reliable computerized image processing method was established to accurately calculate the characteristics and pattern of bone defects in patients with femoral neck fractures. It was clarified that for displaced femoral neck fractures, bone defects are not limited to the posterior cortex, but are also present in other areas. In this study, we found that there was a significant correlation between the severity of the bone defects and the age of the patient. The results of the study could help surgeons in surgical planning for patients whose age is at threshold between internal fixation and arthroplasty Abstract: Background: Bone defects in femoral neck fractures are strongly associated with the prognosis after internal fixation. However, qualitative analysis of bone defects in femoral neck fractures has already been performed, quantitative studies have not been reported. In this study, we aimed to systematically analyse the morphological characteristics of bone defects in patients with femoral neck fractures using computed tomography (CT) images combined with computer image analysis techniques. Methods: Four hundred and sixty-nine patients with femoral neck fractures from January 2014 to December 2018 at two grade A tertiary hospitals were included. Models were created in Mimics software based on CT images collected within 1 week after injury and then imported into 3-matic software for virtual reduction. The volume of the bone defect (VBD), maximum defect thickness (MDT), extent of the bone defect region (EBDR), main defect quadrant (MDQ), collapse type and fracture classification were calculated and recorded. Results: The EBDR, collapse type and MDT all had a significant positive effect on the VBD ( P <0.05), with a more significant effect at higher quantiles. Age also had a significant positive effect on the VBD ( P < 0.05), but its effect was more pronounced at lower quantiles. Compared to non-subcapital fractures, subcapital fractures had a positive effect on the VBD only at the 50 and 75% quantiles ( P < 0.01). The female sex had a significant negative effect on the VBD compared to the male sex ( P < 0.05). Conclusion: This study established a reliable computer image processing method for quantitative analysis of the VBD in femoral neck fractures and revealed that all patients with femoral neck fractures had bone defects, which can occur at any part of the femoral neck. The EBDR, MDT, collapse type, and patient age and sex were all important risk factors for the extent of the defect and should be taken into account in surgical planning.